Formação profissional e emprego: o caso das egressas do curso técnico em vestuário do Cefet-MG, campus Divinópolis - Nogueira, Maria de Lourdes Couto (2010)
This work addresses the relationship between professional training course and job market insertion of a group of alumni of the technical clothing course at Cefet-MG, from 2002 to 2008. The significant presence of women in the course is evident from the time of enrollment in the selection process until its conclusion, which reflects the expression of strong female presence in the clothing industry. One of our goals is to reflect on the view that the corresponding diploma of the course would be the guarantee of getting a job, without any mediation. At CEFET School, a student must attend the courses and traineeship to obtain certification as a technical level. The diploma would facilitate the acquisition or guarantee of employment? This is one of the focuses of our research. The future projections of the student of daytime have continuity in their school career and night school student, in turn, does not always prioritize continuity, preferring to enter the job market. One who is already inserted in the job market demands better qualifications. For analysis, data concerning the professional careers of the interviewees were collected. The selection of the eleven former students was defined from the criterion of being inserted in the job market. The main result obtained with the analysis of the data refers to discrepancies between training and jobs done, because knowledge of the entire production process is not seized